2019
DOI: 10.1186/s12939-019-1041-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of pre-adolescent (5–14 years) acute and chronic undernutrition in Lay Armachiho District, Ethiopia

Abstract: Background In Ethiopia it is documented that 16% of all grade repetitions in primary school and 33.9% childhood deaths are associated with undernutrition. School aged children are often omitted from public health research. Thus, the present study was carried out to find out the prevalence and determinants of pre-adolescent (5–14 years) acute and chronic undernutrition in Lay Armachiho District. Methods In this community based cross-sectional study, anthropometrics, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
2
8
1
Order By: Relevance
“…In this study, children without hand-washing facilities were twice more likely to be stunted than those with hand-washing facilities. This finding is consistent with a study done in Dangila Town [ 15 ], and Lay Armachiho District [ 20 ], Northwestern Ethiopia.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, children without hand-washing facilities were twice more likely to be stunted than those with hand-washing facilities. This finding is consistent with a study done in Dangila Town [ 15 ], and Lay Armachiho District [ 20 ], Northwestern Ethiopia.…”
Section: Discussionsupporting
confidence: 93%
“…But the prevalence was less than in the study conducted in Humbo district, Southern Ethiopia [ [ 12 ]], Gondar town, Northwest, Ethiopia [ [ 21 ]], and East Gojjam Zone, Amhara Regional State Ethiopia [ [ 20 ]] where 57%, 46.1%, and 48.1% of the study subjects were stunted, respectively. It is also lower than other studies conducted in other countries including Tea Garden Workers of Assam 47.4% [ 34 ] and Dhaka City, Bangladesh where 60% [ 35 ] were stunted.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Given orphan children are at highest risk of undernutrition risking their health and development, understanding the level and risk factors of malnutrition among this segment of population is an initial step for averting the problem. 12,13 Although several studies on nutritional status of 2 Nutrition and Metabolic Insights under-5 children in Ethiopia exists, [14][15][16][17][18][19][20][21][22] little is known about orphan children in Ethiopia in general and eastern Ethiopia in particular. Therefore, this study was conducted to assess the prevalence of undernutrition and its associated factors among institutionalized school-age orphans in Harari Regional State, eastern Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Research from Ethiopia, Kenya, South Africa (SA), Malawi and Tanzania observed thinness prevalence rates between 11.0 -36.8%, amongst 10 -19-yearolds 9 -24 . Data from Madagascar, Mozambique, Uganda, Kenya and Ethiopia reported thinness prevalence rates of 3.3 -14.9 % in younger adolescents [25][26][27][28][29][30] . Research from Madagascar further reported that 4.8 % of its adolescent population suffered from concurrent thinness, stunting and underweight Two studies presented data on the change in thinness prevalence over time, with contrasting results.…”
Section: Thinnessmentioning
confidence: 99%